Role of gasdermin D in inflammatory diseases: from mechanism to therapeutics - Cheng, Chak Kwong; Yi, Min; Wang, Li; Huang, Yu (Frontiers in Immunology, 2024)
Inflammatory diseases compromise a clinically common and diverse group of conditions, causing detrimental effects on body functions. Gasdermins (GSDM) are pore-forming proteins, playing pivotal roles in modulating inflammation. Belonging to the GSDM family, gasdermin D (GSDMD) actively mediates the pathogenesis of inflammatory diseases by mechanistically regulating different forms of cell death, particularly pyroptosis, and cytokine release, in an inflammasome-dependent manner. Aberrant activation of GSDMD in different types of cells, such as immune cells, cardiovascular cells, pancreatic cells and hepatocytes, critically contributes to the persistent inflammation in different tissues and organs. The contributory role of GSDMD has been implicated in diabetes mellitus, liver diseases, cardiovascular diseases, neurodegenerative diseases, and inflammatory bowel disease (IBD). Clinically, alterations in GSDMD levels are potentially indicative to the occurrence and severity of diseases. GSDMD inhibition might represent an attractive therapeutic direction to counteract the progression of inflammatory diseases, whereas a number of GSDMD inhibitors have been shown to restrain GSDMD-mediated pyroptosis through different mechanisms. This review discusses the current understanding and future perspectives on the role of GSDMD in the development of inflammatory diseases, as well as the clinical insights of GSDMD alterations, and therapeutic potential of GSDMD inhibitors against inflammatory diseases. Further investigation on the comprehensive role of GSDM shall deepen our understanding towards inflammation, opening up more diagnostic and therapeutic opportunities against inflammatory diseases.